THE EFFECT OF OPERATING CASH FLOW AND DIVIDEND POLICY ON STOCK RETURNS (Empirical Study on Kompas 100 Index Companies 2019-2021) - A. Asrorudin; Didik Setiawan; Edi Muhamad Hidayat; Iin Rosini (Jurnal Ekonomi, 2023)
This research aims to determine the influence of Operating Cash Flow, Dividend Policy, and Stock Returns in companies listed on Kompas 100 in 2019-2021. This type of research is quantitative using panel data obtained from the Indonesia Stock Exchange (BEI). The research was conducted on compass index companies 100. The data sampling technique used purposive sampling, the research samples were 16 companies with observations for 3 years 2019-2021. The results of this research are in line with signaling theory, the smaller the size of a company is considered to provide more reliable data for investors to determine share purchase decisions. The results of this research are consistent with research which shows that it has no effect on stock returns. From the test results it can be concluded that Operating Cash Flow, Dividend Policy, and simultaneously influence Stock Returns. From the test results it can be seen that the Operating Cash Flow variable has a partial effect on Stock Returns. From the test results it can be seen that the Dividend Policy variable partially has no effect on Stock Returns